Associations between Milk and Dairy Product Intake, Urinary Sodium-to-Potassium Ratio, and Socioeconomic Status in Japanese Male Adolescents - Yosuke Nagashima; Akiko Horikawa; Ayana Mitsume; Mari Mori (MDPI AG, 2022)
Although socioeconomic status (SES) may affect children's urinary electrolytic excretion and dietary intakes, few studies have reported the association between SES and urinary sodium (Na)-to-potassium (K) ratio in Japanese adolescents and children. Therefore, this study aimed to investigate the association between SES and urinary Na/K ratio (Analysis 1) and between dietary intake and urinary Na/K ratio to determine the SES effects in children and adolescents (Analysis 2). This cross-sectional study included 168 Japanese male adolescent and child football players. The urinary Na/K ratio was calculated from three spot urinary electrolyte values. Multiple regression analysis was performed in both first and second analyses to assess the associations between SES and the urinary Na/K ratio and between dietary intake and the urinary Na/K ratio for ages 9-12 and 13-15 years separately. The mean urinary Na/K ratio was 4.8, with higher SES associated with a lower urinary Na/K ratio. Our results suggested that urinary Na/K ratios in Japanese child football players were high due to poor childhood diets, and higher SES was associated with lower urinary Na/K ratios. Further, milk and dairy products are associated with the urinary Na/K ratio, independent of SES in children and adolescents.